Rule governing the division pattern in Escherichia coli minB and wild-type filaments. - Jaffé, A (1990)
Escherichia coli minB mutants form anucleate minicells and multinucleate filaments. We show here that the overwhelming majority of nucleate cells contain 2n (n = 0, 1, 2, ...) nucleoids, as determined by 4',6-diamidino-2-phenylindole staining, and 2n (n = 1, 2, 3, ...) copies of the replication origin, as determined by flow cytometry. This shows that division sites are not chosen randomly among the available sites in minB filaments. Similarly, wild-type cells contain 2n nucleoids, both during cell division inhibition and when furazlocillin-induced filaments are allowed to divide. We conclude that the min+ function is only to prevent septation only at polar sites; the placement of internal cell division sites must obey strict rules, which are the same in minB and wild-type cells.